Gyrokinetic study of multiple electrostatic and electromagnetic electron-temperature-gradient modes and relevant transport in tokamak finite βe plasmas - X.R. Zhang; X. Jian; J.Q. Dong; Z.X. Wang; Y.P. Zou; S. Xu; J. Li; Y.Y. Li; S. Zheng; Q.B. Luan; M.K. Han; R.R. Ma; et al. (Nuclear Fusion)
We present a comprehensive study of the multiple electrostatic and electromagnetic electron temperature gradient (ETG) modes with a significant upgrading of the gyrokinetic code HD7. Specifically, the non-adiabaticity of all particle species and the electromagnetic effects are taken into account in the upgraded version. Multiple electrostatic ETG (ES-ETG) modes with conventional and unconventional ballooning mode structures are found to be excited by large temperature gradients. The unconventional modes with mode-index $l$ >0 (where $l$ represents peak number as well as parity in ballooning space) have comparable growth rates with the conventional mode under the specific condition, e.g. $6 < R/{L_{Te}} < 25$ , indicating that unconventional modes are significant in L-mode or pedestal top of H-mode. In addition, different from the phenomenon of ES-ETG, multiple electromagnetic ETG (EM-ETG) modes can be excited with ${k_ϑ }{ρ _s} > 1$ and the transition of the dominant eigenstate is observed. The $l = 1$ EM-ETG mode has an excited threshold of ${β _e} = 0.006$ (the ratio of electron pressure over magnetic pressure), indicating that the electromagnetic effect plays a key role in high $β $ (the ratio of thermal pressure to magnetic pressure) condition. Similar to the typical ES-ETG mode, the novel EM-ETG mode is destabilized by large $R/{L_{Te}}$ and suppressed by sufficiently large (either positive or negative) magnetic shear. Talking about the transport capability, the simulation result reveals that EM-ETG mode induced particle flux is quite low ( ${{{Γ }}_{{\text{ES}} - {\text{ETG}}}} \ll {{{Γ }}_{{\text{EM}} - {\text{ETG}}}} \ll {{{Γ }}_{{\text{ITG}}}}$ ) while the energy flux is non-negligible compared to that induced by ion temperature gradient driven mode. Possible relevance of the results with the transport physics in transport barriers is discussed.